Definition of Optimal Optical Coherence Tomography–Based Stent Expansion Criteria: In-Stent Minimum Lumen Area Versus Residual Stent Underexpansion. (20th September 2022) - Romagnoli, Enrico; Ramazzotti, Vito; Burzotta, Francesco; Gatto, Laura; Marco, Valeria; Paoletti, Giulia; Biondi-Zoccai, Giuseppe; Alfonso, Fernando; Crea, Filippo; Trani, Carlo; Prati, Francesco
Abstract : Background: The mismatch between in-stent minimum lumen area (sMLA) and reference vessel lumen area, defined as stent underexpansion (SU), could be an important determinant of stent failure. We tested the clinical predictive value of absolute sMLA in comparison to relative SU in the context of the CLI-OPCI (Centro Per La Lotta Contro L'Infarto-Optimisation of Percutaneous Coronary Intervention) project registry. Methods: We retrospectively analyzed end procedural optical coherence tomography findings in 1211 patients (1422 lesions) undergoing percutaneous coronary intervention, assessing the prevalence and magnitude of residual SU and exploring correlation with outcome in comparison with sMLA. Results: In our series, both sMLA and SU were related to vessel size and anatomic lesion complexity. When compared with patients without adverse event at follow-up, those experiencing device-oriented cardiovascular events (composite of cardiac death, target vessel myocardial infarction, target lesion revascularization, and stent thrombosis) showed a lower sMLA (5.6±2.1 versus 6.1±2.1 mm 2 ; P =0.011) but a comparable degree of SU (11.6±14.1% versus 11.2±13.3%; P =0.734). The prespecified cutoff value of sMLA <4.5 mm 2, documented in 23.8% of cases, was confirmed as independent outcome predictor for device-oriented cardiovascular events (hazard ratio [HR], 2.05 [95% CI, 1.5–2.9]) including target lesion revascularization (HR, 2.43 [95% CI, 1.7–3.5]) and stent thrombosis (HR, 3.23 [95% CI, 1.7–6.3]). A residual SU of 10%, 20%, and 30% was observed in 38.0%, 18.2%, and 7.6% of cases, respectively. No grade of residual SU significantly increased the risk of stent failure, unless if an SU >20% was associated with an sMLA <4.5 mm 2 (HR, 3.11 [95% CI, 1.7–5.6]). Finally, an association between stent overexpansion (ie, >110%) and device-oriented cardiovascular events was also observed (HR, 1.60 [95% CI, 1.1–2.3]). Conclusions: Final absolute sMLA and not relative SU was associated with an increased risk of stent failure. A variable grade of SU was common, but it resulted in being clinically relevant only when associated with an sMLA <4.5 mm 2 .